APPLICATION OF THE WEIGHTED-SUM-OF-GRAY-GASES MODEL TO NON-HOMOGENEOUS H2O/CO2 MIXTURES FOR MEDIA WITH NON-GRAY WALLS - Fonseca, R. J. C. da; França, F. H. R. (Revista de Engenharia Térmica, 2018)
The spectral modeling of the thermal radiation in participating media is a research area that has received constant attention due to its importance in a great number of engineering problems, especially because the highly irregular spectral dependence of the absorption coefficient of a gas with the wavenumber requires the adoption of alternative methods to determine the radiative properties. This work brings a numerical study of a one-dimensional system, bounded by perfectly diffuse and non-gray walls, filled by a non-homogeneous and non-isothermal mixture of water vapor and carbon dioxide. The main objective is to estimate the magnitude of the deviations in treating surfaces that should be considered non-gray as black or gray. The spectral modeling of the problem is performed by the weighted-sum-of-gray-gases (WSGG) model and the accuracy of the solution methodology developed is evaluated by means of comparisons against the results obtained by line-by-line (LBL) integration.